Stacking disorder in metastable NiSn4. (5th November 2016) - Schimpf, C.; Kalanke, P.; Shang, S.L.; Liu, Z.K.; Leineweber, A.
Abstract: The atomic structure of NiSn4 intermetallic forming at ambient temperature in different types of Sn/Ni diffusion couples was investigated by powder X-ray diffraction. The recorded diffraction patterns show narrow Bragg reflections as well as characteristic broad diffraction bands indicative of stacking disorder in the crystal structure of NiSn4 . The crystal structure consists of NiSn 4 layers with square-antiprismatic coordination of Ni by Sn. The stacking of these layers is irregular (faulted) by being an intermediate between the pseudotetragonal PtSn4 - (space group Aeaa ) and the tetragonal β-IrSn4 -type (space group I 41 / acd ) ideal structures. Thereby, the shape of the diffraction bands reveals that the stacking more closely corresponds to β-IrSn4 - than to the PtSn4 -type. The obtained lattice parameters are: a (β-IrSn4 ) = a (PtSn4 ) = b (PtSn4 ) = (6.248 ± 0.001) Å and 2 c (PtSn4 ) = c (β-IrSn4 ) = (23.001 ± 0.004) Å. Pronounced stacking corresponding to a PtPb4 -type structure discussed in the literature is not present in NiSn4 on the basis of the diffraction data. The latter finding is compatible with density functional theory (DFT) based first-principles calculations, indicating a higher energy for PtPb4 -type NiSn4 as compared to PtSn4 - and β-IrSn4 -type NiSn4 . Graphical abstract: Highlights: Growth of metastable NiSn4 in Sn/Ni diffusion couples produced in different ways Clarification of the crystal structure of NiSn4 Modelling of X-ray diffraction patterns of faulted NiSn4 fully explaining the observed patterns Critical review of previously published reports on NiSn4